2017
DOI: 10.3415/vcot-16-06-0096
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative computed tomography and low-field magnetic resonance imaging findings in dogs with degenerative lumbosacral stenosis treated by dorsal laminectomy

Abstract: The study indicates that imaging signs of neural compression are common after DLSS surgery, even in dogs that have clinical improvement. Contrast enhancement of spinal nerves and soft tissues around the region of disc herniation is common both pre- and postoperatively and thus are unreliable criteria for identifying complications of the DLSS surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The VP, which refers to the presence of gas in the IVD, is a relatively common radiological finding in humans and dogs, especially from CT, with an incidence of 6% in canine vertebral CT scans (14, 16, 22, 30, 31). Although an intervertebral VP can indicate vertebral disc degeneration and herniation, it should not be considered a unique identifier for spinal compression.…”
Section: Discussionmentioning
confidence: 99%
“…The VP, which refers to the presence of gas in the IVD, is a relatively common radiological finding in humans and dogs, especially from CT, with an incidence of 6% in canine vertebral CT scans (14, 16, 22, 30, 31). Although an intervertebral VP can indicate vertebral disc degeneration and herniation, it should not be considered a unique identifier for spinal compression.…”
Section: Discussionmentioning
confidence: 99%
“…19/20 studies clearly reported age, breed, and sex, of the participants. Weight (28)(29)(30)(31) and level of activity (4, 32) were additionally reported in some studies. 13/20 included studies did not clearly report duration and presence of clinical signs among the participants.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…In applications where high electric or magnetic fields are required, optical fiber based headphones and microphones are very useful. These applications include team communication among medics working on a patient in an MRI (Magnetic resonance imaging) system during surgeries that are MRI-guided [ 72 ]. In oil industries, optical fibers are used to measure temperature and pressure in oil wells [ 73 , 74 ].…”
Section: Classification Of Optical Fiber Sensorsmentioning
confidence: 99%